2014
DOI: 10.3109/07420528.2014.917090
|View full text |Cite
|
Sign up to set email alerts
|

Differential circadian pattern of water and Na excretion rates in the metabolic syndrome

Abstract: This study comparatively investigated the chronobiology of water and Na excretion rates (W-ExcR and Na-ExcR) in 46 non-diabetic metabolic syndrome (MS) patients. The circadian pattern of W-ExcR was independently associated with the nocturnal dipping of systolic blood pressure (β = -3.1). During oral glucose tolerance test, the rise in plasma insulin (β = 34.0) and the insulinogenic index (β = 4.1) were independently associated with the day/night ratio of W-ExcR. The circadian pattern of Na-ExcR was not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They showed that the circadian pattern of urine flow rate/urine concentration and/or sodium excretion rate may be disturbed in some subjects. An excessive urine concentration during daytime, limiting sodium and/or water excretion rate, is subsequently compensated at night by the pressure-natriuresis mechanism [59,60,61,62,63]. Accordingly, measurement of U osm in overnight urine samples may not be representative of 24-h urine.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that the circadian pattern of urine flow rate/urine concentration and/or sodium excretion rate may be disturbed in some subjects. An excessive urine concentration during daytime, limiting sodium and/or water excretion rate, is subsequently compensated at night by the pressure-natriuresis mechanism [59,60,61,62,63]. Accordingly, measurement of U osm in overnight urine samples may not be representative of 24-h urine.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, potassium excretion is relatively fast compared with that of other electrolytes. In rats and humans, the excretion rate of potassium during daytime is about three times higher than that during nighttime, a much higher day/night ratio than that observed for water and sodium, while creatinine is excreted almost at the same rate during day and night (55,70,152,176). Several studies also showed that potassium excretion increases rapidly after an acute intake of potassium, independently of any change in aldosterone level.…”
Section: Possible Role Of the ␣-Cell And Glucagon In Potassium Homeostasismentioning
confidence: 96%
“…Unfortunately, this 'knowledge' does not mean that the effects can, consequently, be successfully treated, since this depends on the particular nature of the core problem causing the disorder. Obesity often carries with it severe additional consequences, including the loss of mobility [341,342] and misadjusted water/electrolyte handling [343] or thermoregulation [344,345]. Some of these effects can be attributable simply to the effect of the extra body mass to be held, physically supported/carried, and provided with adequate nutrients and oxygen supply through an (also altered) blood flow; a burden additional to the metabolic and regulatory distortions that cause the obesity hypertrophic and/or hyperplastic disordered growth.…”
Section: Other Aspects Of Msmentioning
confidence: 99%